Legal and ethical considerations of artificial intelligence in skin cancer diagnosis. (18th August 2021) - Jobson, Dale; Mar, Victoria; Freckelton, Ian
Abstract: Artificial intelligence (AI) technology is becoming increasingly accurate and prevalent for the diagnosis of skin cancers. Commercially available AI diagnostic software is entering markets across the world posing new legal and ethical challenges for both clinicians and software companies. Australia has the highest rates of skin cancer in the world and is poised to be a significant benefactor and pioneer of the technology. This review describes the legal and ethical considerations raised by the emergence of artificial intelligence in skin cancer diagnosis and proposes recommendations for best practice.